Free, Fair and Transparent Election in India: Issues and Challenges (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Free, fair and transparent election is the soul of democracy but anonymity of the contributor to the political parties is an essential element of electoral bond scheme. Money influence electoral politics, vote buying and electoral expenditure. Money creates entry barrier to politics, exclusionary impact by reducing the democratic space for preparation of candidates, financial superiority translating into electoral advantage and disclosure of political funding to the public is essential element of democracy. Transparent and accountable governance is fundamentals of democracy.